Quadri-Cluster Broadband Circularly-Polarized Sequentially-Rotated Metasurface-Based Antenna Array for C-Band Satellite Communications - Supreeyatitikul, Nathapat; Torrungrueng, Danai; Phongcharoenpanich, Chuwong (My University, 2021)
This research proposes a compact quadri-cluster broadband circularly polarized (CP) sequentially-rotated metasurface-based (MTS) antenna array for the C-band frequency spectrum. One cluster of the quadri-cluster MTS-based antenna array consisted of 4 times 4 S-shaped periodically-arranged MTS elements. The sequentially-rotated feed network was utilized to realize circular polarization and improve the impedance bandwidth (IBW), 3-dB axial ratio bandwidth (ARBW) and 3-dB boresight gain bandwidth of the quadri-cluster MTS-based antenna array. Simulations were performed and results were compared with experiments. The measured IBW and ARBW were 84.74% (4.0-9.0 GHz) and 57.6% (4.2-7.6 GHz) at the center frequency of 5.9 GHz, rendering the proposed quadri-cluster MTS-based antenna array suitable for satellite communication applications. In addition, the quadri-cluster MTS-based antenna array achieved the measured 3-dB boresight gain bandwidth of 81.3% (3.9-8.7 GHz), the maximum gain of 10.04 dBic at 5.6 GHz, and low radar cross-section. Specifically, the novelty of this research lies in the use of the sequentially-rotated feed network with the S-shaped MTS elements to effectively enhance ARBW of the quadri-cluster MTS-based antenna array for the C-band frequency spectrum.
Keywords: Antenna array; C-band; circular polarization; metasurface; sequentially-rotated feed network